Multimodal Images of Acute Central Retinal Artery Occlusion. (16th November 2017) - Shah, Parth; Schwartz, Stephen G.; Flynn, Harry W.
Abstract : Two illustrative cases of acute central retinal artery occlusion (CRAO) are presented with multimodal imaging, including fluorescein angiography (FA) and commercially available optical coherence tomography angiography (OCT-A). In both patients, retinal ischemia was imaged well using both FA and OCT-A, and the two imaging studies provided comparable pictures. OCT-A provides useful information for the diagnosis and management of patients with acute CRAO, without the need for dye injection.